1997
DOI: 10.1086/513655
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Ocular Complications in Orthotopic Liver Transplant Patients

Abstract: We report the frequency and type of infectious ocular complications following orthotopic liver transplantation (OLT) and review diagnostic and therapeutic strategies. During the period September 1988 through November 1994, 684 patients underwent OLT at Mount Sinai Hospital (New York). Nine orthotopic liver transplant patients (1.3%) developed ocular infections: Candida albicans endophthalmitis (2), Aspergillus fumigatus endophthalmitis (1), cytomegalovirus retinitis (4), herpes simplex virus keratitis (1), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…It has previously been shown that in iatrogeniThis threshold may be unchanged for new disease, since the incidence of CMV has decreased in patients responding to cally immunosuppressed transplant patients, immune recovery can be accomplished by decreasing the dose of immunosuppotent antiretroviral combinations. For established CMV retinitis, we have observed at both institutions unusually long periods pressive medications [22]. The lack of reactivation without specific anti-CMV maintenance in all 11 patients at two sepaof retinitis inactivity, even in patients treated with oral ganciclovir and who experienced more modest rises in CD4 cell rate institutions, during a median observation of 156 days, supports the hypothesis that AIDS patients responding to counts (between 45 and 60/mm 3 ), suggesting that a modification of the history of treated disease may have occurred.…”
Section: Resultsmentioning
confidence: 97%
“…It has previously been shown that in iatrogeniThis threshold may be unchanged for new disease, since the incidence of CMV has decreased in patients responding to cally immunosuppressed transplant patients, immune recovery can be accomplished by decreasing the dose of immunosuppotent antiretroviral combinations. For established CMV retinitis, we have observed at both institutions unusually long periods pressive medications [22]. The lack of reactivation without specific anti-CMV maintenance in all 11 patients at two sepaof retinitis inactivity, even in patients treated with oral ganciclovir and who experienced more modest rises in CD4 cell rate institutions, during a median observation of 156 days, supports the hypothesis that AIDS patients responding to counts (between 45 and 60/mm 3 ), suggesting that a modification of the history of treated disease may have occurred.…”
Section: Resultsmentioning
confidence: 97%
“…A large series from New York City found CMV retinitis in 4 of 684 liver transplant recipients [91]. Symptoms began, on average, 4 months after transplantation.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…4,10 Ocular infection after renal, cardiac, or bone marrow transplantation is reported between 1.3-5%. 6,[11][12][13] Elevated intraocular pressure is rarely observed, occurring in 1-2% of patients with prolonged oral steroid therapy after transplantation. 5,6,14 Similar data, however, are poorly documented in the pediatric age group.…”
mentioning
confidence: 99%